PENERAPAN MODEL PEMBELAJARAN ROPES (REVIEW, OVERVIEW, PRESENTATION, EXERCISE, SUMMARY) UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF KELAS XI SMA PADA MATERI GELOMBANG BUNYI - Adinda Nurul Aini; Muhammad Nor; Dedi Irawan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The ROPES learning model is a learning model with a complete and interrelated series of activities that can improve students' abilities and active roles in learning. The purpose of this study was to determine the cognitive learning outcomes of class XI high school students by applying the ROPES learning model to sound wave material. The type of research used is experimental research with the "True experimental design" method with the form of research design "Post-test only control design". This research was conducted at MAN 1 Pekanbaru with a total sample of 62 students consisting of 32 students of class XI IPA RISET 2 as the experimental class and 30 students of class XI IPA IT as the control class. The data collection instrument was in the form of a cognitive learning outcome test for sound waves consisting of 20 multiple choice questions. The data analysis used is descriptive analysis in the form of student absorption and inferential analysis in the form of data normality test, data homogeneity test, and hypothesis testing with the Mann Whitney test assisted by SPSS version 26. The results of this study indicate that the cognitive learning outcomes of experimental class students are based on absorption capacity. better than the control class and there is a significant difference in students' cognitive learning outcomes between the experimental class that applies the ROPES learning model and the control class that applies the conventional learning model.Keywords: Cognitive Student Learning Outcome, ROPES Learning Model, Sound Wave